"The postman" and Skinner: a study of metaphor. (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
In the present study, some variables that might have controlled use of metaphor by characters from the movie Il Postino: The Postman are listed. For example, when the character says "I felt like a boat shaken by the words", we suggest that the effect he felt when he listened to the poem was similar to the effect he felt when he was in a boat, on the open sea. When he was in the boat and when he listened to the poem, he experienced nausea. In this article, metaphors are differentiated from standard responses, which are already commonly used in the verbal community. We suggest that the reciting of poems by the postman has the function of manding; as a consequence, he is drawn closer to the woman he loves. Echoic and intraverbal verbal operants are also presented, because they are useful concepts in analyzing the reproduction of poems previously created by the poet.
Keywords: Private events; Metaphor; Radical behaviorism; "Il Postino"; Tact